Challenges of Criminal Liability Related to Artificial Intelligence (AI) in Indonesia: Lessons from European Law - Tahir, Ach. (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to analyze the reasons why Indonesian criminal law has not yet recognized Artificial Intelligence (AI) as a subject of criminal liability and to examine relevant models of criminal responsibility when AI is involved in criminal acts. This research employs a normative legal method with a literature-based approach, analyzing legislation, criminal law doctrines, and international literature related to the development of AI regulation. The analysis shows that the difficulty in positioning AI as a legal subject stems from juridical, philosophical, and technical limitations within Indonesian criminal law. As a solution, when AI-related crimes occur, criminal liability may be attributed to programmers, manufacturers, users, or corporations based on their degree of functional control over the AI system. This approach is compared with the regulatory framework of the European Union through its AI Act, which serves as a normative benchmark as the first comprehensive and binding AI regulation addressing accountability in autonomous systems. The relevance of this comparison lies in its emphasis on control-based and risk-oriented responsibility, which reflects legal challenges similarly faced within the Indonesian legal system and aligns with the doctrines of functional control, corporate liability, vicarious liability, and risk management. The study concludes that Indonesia's current criminal law framework does not place AI as a subject of criminal law, thereby directing liability toward humans or corporations within the technology's control chain.